In search of consensus in education: the experience of the LOE - Tiana Ferrer, Alejandro (Avances en Supervisión Educativa, 2010)
The coming in force of the 2006 Organic Act of Education (LOE) put an end to laborious task of study of all the educational regulations. Throughout that process, one of the demands more frequently requested by educational segments of society was the need of undertaking a contract on Education, one that was able to avoid the swinging of educational regulations and the application of new and politically orientated instructions in Education.